2014
DOI: 10.1016/j.rbr.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Exposição à periodontite no intervalo de um ano antes do tratamento antidiabético e risco de artrite reumatoide em pacientes com diabete mellitus: estudo de coorte populacional

Abstract: PD exposure within one year before anti-diabetic treatment was associated with increased RA risk in newly treated DM patients. The lack of knowledge about individual smoking status is a major limitation of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…A dose–response relationship between PD and RA risk was also observed when PD-related utilizations were used as the proxy measures of PD severity. Consistent with the findings of two recent case-control studies [ 19 , 21 ] and one population-based diabetic cohort study [ 20 ], the results of this cohort study suggested that PD exposure is associated with a greater risk of RA development. In our previous case-controlled study, the risk of RA associated with PD exposure (odds ratio, 1.16; 95% CI, 1.12–1.20) was lower than that estimated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…A dose–response relationship between PD and RA risk was also observed when PD-related utilizations were used as the proxy measures of PD severity. Consistent with the findings of two recent case-control studies [ 19 , 21 ] and one population-based diabetic cohort study [ 20 ], the results of this cohort study suggested that PD exposure is associated with a greater risk of RA development. In our previous case-controlled study, the risk of RA associated with PD exposure (odds ratio, 1.16; 95% CI, 1.12–1.20) was lower than that estimated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Other potential confounders included CCI as adapted by Deyo et al 54 , periodontitis as defined in our previous study 18 , and the use of statin drugs for ≥28 days within the year prior to the index date. Periodontitis was selected because it has been found to increase the risk of RA 17 18 . Statins were chosen as a potential confounder because their persistent use has been reported to reduce the RA risk 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the Taiwanese National Health Insurance Research Database (NHIRD) made population-based longitudinal studies feasible. We have successfully utilized the NHIRD to conduct several epidemiologic studies of RA 16 17 18 . The first part of the present study aimed to conduct a population-based, matched case-control study to examine the potential RA-protective effect of acarbose using the NHIRD.…”
mentioning
confidence: 99%